Aplikasi Game Edukasi: Meningkatkan Pembelajaran dan Minat Belajar Remaja Di GGP Sanggabuana - Sri Rezeki (Jurnal Silih Asih, 2024)
This paper discusses the importance of using educational gaming applications to enhance adolescent learning at GGP Sanggabuana. In this era of rapid technological advancement, educational gaming applications have become an innovative solution to facilitate interactive and enjoyable learning for children. The benefits of using these applications include increased interest in learning, reinforcement of teaching through visual and auditory interaction, facilitation of self-directed learning, provision of instant feedback, and reinforcement of positive collaboration and competition. The steps for implementing educational gaming applications at GGP Sanggabuana include needs assessment, application development, training and mentoring, integration with the curriculum, monitoring and evaluation, and collaboration with parents. By involving all stakeholders, educational gaming applications can be optimized in enhancing children's interest and effectiveness in learning within the context of religious education. However, it is important to conduct further research and evaluation on the effectiveness and benefits of educational gaming applications in adolescent learning. This is necessary to continue developing and improving the quality of applications, so that children's learning experiences can further enhance their understanding of religious and moral values. With the existence of educational gaming applications, it is hoped that children can experience more engaging, interactive, and meaningful learning experiences in the context of adolescence at GGP Sanggabuana.